Analisis Kemampuan Dan Kinerja Keuangan Pemerintah Daerah Kota Tanggerang Tahun Anggaran 2016-2020 - Fajri, Ahmad; Munandar, Agus (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2021)
The purpose of this study is to analyze the capability and financial performance of the Tangerang City Government. Financial capability analysis is carried out using two approaches: Ratio Analysis of Fiscal Autonomy Degrees (DOF) and Routine Ability Index (IKR). Financial performance analysis is carried out using two approaches: Effectiveness Ratio Analysis of Regional Original Income (PAD) and the Independence Ratio. The results obtained are the ability and financial performance of the Tangerang City Government in the period 2016 to 2020 seen from the DOF Ratio, IKR Ratio, PAD Effectiveness Ratio, and Independence Ratio which significantly shows good results. With the ratio of Degrees of Fiscal Autonomy (DOF) it can be seen that Tangerang City's Original Regional Revenue (PAD) has sufficient ability to contribute to overall regional income. The IKR ratio shows that the Tangerang City Government has been able to finance its routine expenditures through Local Revenue. Through the Effectiveness ratio, it can be seen that the Tangerang City government has effectively succeeded in realizing its original regional revenue target. Finally, by using the independence ratio, it shows that the Tangerang City government has succeeded in having a high level of independence in terms of financing government activities, development, and services to the community.